Proofreading of ribonucleotides inserted into DNA by yeast DNA polymerase ε - Williams, Jessica S. (2012)
We have investigated the ability of the 3′ exonuclease activity of S. cerevisiae DNA polymerase ε (Pol ε) to proofread newly inserted ribonucleotides (rNMPs). During DNA synthesis in vitro, Pol ε proofreads ribonucleotides with apparent efficiencies that vary from none at some locations to more than 90% at others, with rA and rU being more efficiently proofread than rC and rG. Previous studies show that failure to repair ribonucleotides in the genome of rnh201Δ strains that lack RNase H2 activity elevates the rate of short deletions in tandem repeat sequences. Here we show that this rate is increased by 2–4-fold in pol2–4 rnh201Δ strains that are also defective in Pol ε proofreading. In comparison, defective proofreading in these same strains increases the rate of base substitutions by more than 100-fold. Collectively, the results indicate that although proofreading of an ‘incorrect’ sugar is less efficient than is proofreading of an incorrect base, Pol ε does proofread newly inserted rNMPs to enhance genome stability.